2018
DOI: 10.1016/j.ultsonch.2018.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Study on regeneration effect and mechanism of high-frequency ultrasound on biological activated carbon

Abstract: High frequency ultrasonic radiation technology was developed as a novel and efficient means of regenerating spent biological activated carbon (BAC) used in drinking water treatment plants (DWTPs). The results of this study indicated that high frequency ultrasonic treatment could recover the spent BAC, to some extent, with the following optimal conditions: a frequency of 400 kHz, sonication power of 60 W, water temperature of 30 °C, and sonication time of 6 min. Under the above conditions, the iodine value incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…The adsorption capacity of iodine, methylene blue, phenol and the iron content of the prepared MAC were determined according to the test methods for wooden activated carbon described in the National Standard of China, [31][32][33][34] GB/T 12496.8-2015, GB/T 12496.10-1999, GB/T 12496.12-1999 and GB/T 12496.19-2015, respectively.…”
Section: Characterization Of the Prepared Macmentioning
confidence: 99%
“…The adsorption capacity of iodine, methylene blue, phenol and the iron content of the prepared MAC were determined according to the test methods for wooden activated carbon described in the National Standard of China, [31][32][33][34] GB/T 12496.8-2015, GB/T 12496.10-1999, GB/T 12496.12-1999 and GB/T 12496.19-2015, respectively.…”
Section: Characterization Of the Prepared Macmentioning
confidence: 99%
“…Qian et al [22] found decreasing of Nitrospira from 0.44% to 0.04% by DO level of 0.8-1.5 mg-O 2 L -1 with SRTs between 33 and 56 d and NH 4 + 105 mg-N/L. While Sun et al [23] set a short SRT of 15 d with DO concentration at 1.0 and 2.0 mg-O 2 L -1 that increased 1.81 and 2.99%, respectively. Under the longer SRT (30 d) with the DO level (0.7-1.1 mg-O 2 L -1 ) at TH1 presented low abundance of Nitrospira than Nitrobacter, while the three plants with the shorter SRT (17 to 26 d) and higher DO level of 2.4 -4.5 mg-O 2 L -1 presented high abundance of Nitrobacter than Nitrospira.…”
Section: Nitrogen-cycling Microbial Abundances and Communitiesmentioning
confidence: 95%
“…During the collection of all samples of this work, the temperature was recorded from 18.5 to 28 • C. For this reason, the optimal temperature ranges for Nitrobacter and Nitrospira growth are not exactly reported. Huang et al [7] concluded that Nitrobacter was the favorable species under the temperature ranges of 24-25 • C while Nitrospira dominated at a relatively high temperature range of 29-30 • C. On the contrary, Alawi et al [34] indicated that a lower temperature range of 10-20 • C was the optimum condition for Nitrospira growth.…”
Section: Nitrite-oxidizing Bacteria (Nob) Targetingmentioning
confidence: 99%